Outcomes of Contemporary Family Screening in Hypertrophic Cardiomyopathy - van Velzen, Hannah G; Schinkel, Arend F L; Baart, Sara J; Oldenburg, Rogier A; Frohn-Mulder, Ingrid M E; van Slegtenhorst, Marjon A; Michels, Michelle (Circulation. Cardiovascular genetics, 2018)
Contemporary hypertrophic cardiomyopathy (HCM) family screening includes clinical evaluation and genetic testing (GT). This screening strategy requires the identification of a pathogenic mutation in the proband. Our aim was to examine the results of this HCM screening strategy. Between 1985 and 2016, 777 relatives of 209 probands were assessed in the context of HCM screening. Genotype-positive (G+) relatives and relatives without genetic testing (GT) underwent repeated clinical evaluations. In genotype-negative (G-) relatives mortality was assessed during follow-up. A pathogenic mutation was identified in 72% of probands. After counseling, GT was performed in 620 (80%) relatives: 264 (43%) were G+ (age 41±18 y) and 356 (57%) were G- (age 48±17 y). At first screening, HCM was diagnosed in 98 (37%) G+ relatives and 28 (17%) relatives without GT ( <0.001). During 9 years follow-up of relatives diagnosed with HCM, 8 (6%) underwent septal reduction therapy, 16 (16%) received primary prevention ICDs, and cardiac mortality was 0.3%/year. During 7 years follow-up of relatives without HCM, 29 (16%) developed HCM. Survival at 5/10 years was 99%/95% in G+ relatives, 97%/94% in G- relatives ( =0.8), and 100%/100% in relatives without GT. HCM was identified in 30% of relatives at first screening, and 16% developed HCM during 7 years of repeated evaluation. GT led to a discharge from clinical follow-up in 46% of the study population. Survival in the relatives was good.